Theory of gateway in case of time travel - Ahamed, Sahriar (International Journal of Advanced Astronomy, 2019)
When we record any video, where do we keep and store it? In a space- that we call memory card or disk or any other kind of storage device. When we are required to see our memories, what we do? We play it with a video player software which is known as media player, dvd player or video player etc. These video player software works as the gate way to visualize the past in-front of us. Same way our reality is storing in another place/space which is another dimension that we know as our past. We can always see it by creating a gate way same as video player software or we may say it as knowledge.Â Â